PENGARUH BUDAYA MUTU, TINGKAT QUALITY OF WORK LIFE (QWL) DAN KNOWLEDGE MANAGEMENT TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) : (STUDI PADA KARYAWAN PT. AVIAN AVIA) - Wahyu Eko Pujianto; Evendi (Universitas Nahdlatul Ulama Sidoarjo, 2021)
The purpose of the research is to prove and analyze the influence of quality culture, level of quaity of work life and knowledge management on organizational citizenship behavior in employees of PT. Avian Avia. The research was conducted with a quantitative approach, with the sample analyzed, namely 179 employees of the production division. The data analysis technique used is multiple linear regression analysis. The results of the study prove that quality culture, quaity of work life and knowledge management both partially and simultaneously have a significant contribution to organizational citizenship behavior. Other results show that the influence of quality culture, quaity of work life and knowledge management on organizational citizenship behavior is 74.4%.